One- and Three-Screen Driving Simulator Approaches to Evaluate Driving Capacity: Evidence of Congruence and Participants' Endorsement. - Gibbons, Carrie; Mullen, Nadia; Weaver, Bruce; Reguly, Paula; Bédard, Michel (American Journal of Occupational Therapy)
OBJECTIVE. We examined the validity of one-screen versus three-screen driving simulators and their acceptability to middle-aged and older drivers. METHOD. Participants aged 40-55 or 65 and older (N 5 32) completed simulated drives first with a single monitor and then with a three-monitor setup, followed by pen-and-paper measures and an interview. RESULTS. Mean differences between one- and three-screen drives were not statistically significant for Starting/Stopping and Passing/Speed. Correlations between the two drives indicated moderate positive linear relationships with moderate agreement. More errors occurred on the one-screen simulator for Signal Violation/Right of Way/Inattention, Moving in a Roadway, Turning, and Total Scores. However, for Moving in a Roadway, Turning, and Total Scores, correlations between drives indicated strong positive linear relationships. We found no meaningful correlation between workload, computer comfort, simulator discomfort, and performance on either drive. Participants found driving simulators acceptable. CONCLUSION. Findings support the use of one-screen simulators. Participants were favorable regarding driving simulators for assessment.